Application of Picture Media in Improving Children's Speaking Ability at Zivana Monte Sori Makassar City (JED (Jurnal Etika Demokrasi), 2023)
The problem in this study is whether the application of media images improves children's speaking skills at Zivana Monte Sori Makassar City. The purpose of this study is to find out whether the application of media images can improve speaking skills in children at Zivana Monte Sori, Makassar City. Research was conducted using a type of classroom action research (CAR). The research procedure consists of planning, implementing, observing, and reflecting. Based on the results of research conducted at Zivana Monte Sori, Makassar City, the results of children's speech development were obtained, as evidenced by an increase in the average child's speaking ability during pre-action cycle I. The results showed that children who developed very well (BSB) were 4 children (16%), then in the second cycle of action the results were 10 children (40%) who developed very well (BSB), and in the third cycle the results were 16 children (64%) who developed very well (BSB). This means that the average increase in children's speaking ability through the media of images during pre-action, Cycle I, Cycle II, and Cycle III is very significant in its improvement.